GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG MANAJEMEN LAKTASI DI ASRAMA BATALYON ZENI TEMPUR 18/YKR GIANYAR - Dewa Putu Eka Putra Apnyana; Putu Intan Daryaswanti (Bali Health Published Journal, 2020)
Background: Lactation management is all management and efforts made to help mothers achieve success in breastfeeding their babies properly. The lack of proper management of lactation results in a decrease in the immune system of the baby, an increase in malnutrition and malnutrition rates that are at risk of increasing morbidity and mortality in infants. This study aims to determine the knowledge of mothers about lactation management in the Battalion Zeni Tempur 18 / YKR Gianyar Dormitory in 2020 Method: This research used descriptive research method with survey approach. The population in this study were mothers who had children under five in the Battalion Engineer Battalion 18 / YKR Gianyar Dormitory with a total sample of 37 samples. The sampling technique used in this study was purposive sampling. Results: The results of 37 respondents, that is the knowledge of mothers about lactation management, mostly in the good category. Respondents aged 20-35 years were mostly 32 people (91.4%) had good knowledge. Respondents with a high level of education were mostly 24 people (92.3%) with good knowledge. Respondents who did not work were mostly 22 people (88%) who had good knowledge. Primiparous respondents mostly 22 (88%) had good knowledge about lactation management. Conclusion: The level of mother's knowledge about lactation management in the Battalion Engineer Battalion 18 / YKR Gianyar Dormitory is mostly in the good category of 34 people (91.9%)